Maximum time between cardiac cycles in atrial fibrillation for assessing the risk of arterial thromboembolism - O. A. Germanova; A. V. Germanov; Yu. V. Shchukin (Российский кардиологический журнал)
Aim. To assess the development of thromboembolic events in different types of atrial fibrillation (AF), which differ in the maximum time between cardiac cycles.Material and methods. The main group included 80 patients with permanent AF, while the control one — 88 people without AF. The following investigations were performed: echocardiography, 24-hour electrocardiographic (ECG) monitoring; ultrasound of extracranial arteries, aortic branches, lower limb arteries; sphygmography of the common carotid and posterior tibial arteries. If required, coronary angiography, cerebral angiography, brain computed tomography were performed. According to 24-hour ECG monitoring, all patients of the main group were divided into 2 subgroups (A and B) depending on the maximum time between cardiac cycles in AF: subgroup A (n=42) — patients with a maximum time between cardiac cycles <1,5 seconds, subgroup B (n=38) — ≥1,5. The followup period lasted 1 year. During the follow-up period, the development of arterial thromboembolic events was analyzed.Results. The patients were comparable in key paraclinical characteristics and comorbidity profile. One-year follow-up period revealed a significantly higher incidence of stroke, transient ischemic attack, myocardial infarction, and distal arterial embolism of lower limb arteries in subgroup B. With an increase in the maximum time between cardiac cycles in AF, an increase in hemodynamic parameters of arterial vessels occurred as both proximal and distal arteries. A similar trend was also observed in the analysis of arterial kinetic parameters.Conclusion. Not only the fact of AF presence is important for assessing the risk of arterial thromboembolism, but also its features. The most unfavorable for prognosis is AF with a maximum time between cardiac cycles ≥1,5 seconds. An increase in intra-arterial hemodynamic parameters after a long pause between ventricular contractions in AF without intracardiac thrombosis can become a key factor in the development of complications with existing plaques, which can become a source of distal embolism.